TP53 Gene 72 Arg/Pro (rs1042522) single nucleotide polymorphism increases the risk and the severity of chronic lymphocytic leukemia - Ounalli, Asma; Moumni, Imen; Mechaal, Amal; Chakroun, Aya; Barmat, Mbarka; Rhim, Rim El Elj; Menif, Samia; Safra, Ines (Frontiers in Oncology, 2023)
Background: Genetic variations in TP53 gene are known to be important in chronic lymphocytic leukemia (CLL) and may cause its inactivation which is associated with an aggressive form of the disease. Single nucleotide polymorphism (rs1042522 :G>C) in TP53 gene at codon 72 encodes for arginine (Arg) or proline (Pro) variant which results in amino acid substitution affecting the apoptotic potential of TP53 protein. The aim of this study was to assess the correlation between TP53 codon 72 polymorphism and risk susceptibility as well as severity of CLL among Tunisian patients.A case-control study was conducted in Tunisia from February 2019 to November 2021, 160 de novo CLL patients and 160 healthy volunteers matched in age and gender were involved. DNA was extracted from peripheral blood mononuclear cells and the rs1042522 was analyzed using PCR-RFLP.Results: Pro variant was associated with higher susceptibility to CLL than Arg variant (p= 0.023). A significant association was found between Pro variant and prognostic classification of Binet stage C (p= 0.001), low hemoglobin level (p= 0.003) and low platelet count (p= 0.016).We suggest that Pro variant may increase the risk of developing CLL in our population and could be associated with the severity of the disease.